Movilización transnacional indígena en la cuenca amazónica: democracia, nuevos movimientos sociales y comunidades epistémicas (Tema Central) - Florêncio, Jéssica Girão (2018)
The growing discussion regarding social movements in the hegemonic context of liberal democracies, as well as the increasing number of groups organized for different reasons, raises questions about the States’ apparatuses for the maintenance of democracy. This paper aims to discuss the emergence of social movements in the context of transnationality and epistemic communities. Thus, the theories about democracy and social movements are addressed. The reasons why these social groups articulate are also analyzed, with emphasis on indigenous articulations, even in the category of new transnational social movements. These groups are conceptualized as transnational networks and epistemic communities, based on the discussions of critical constructivism.